THE EFFECT OF FLIPPED CLASSROOM STRATEGY IN IMPROVING STUDENTS’ SELF-REGULATION LEARNING - Feny Martina; Zelvia Liska Afriani; Latifatul Jannah (International Journal of Research on English Teaching and Applied Linguistics, 2022)
This study investigates the flipped classroom strategy that will be used by an English teacher to improve students' self-regulation. This study uses a quasi-experimental method. The data were collected using self-regulation measurement questionnaires. The questionnaires distributed to the students were adopted from ADPI of (1989) about self-regulation. The number of questionnaires is 28 statements consist of three aspects, namely, cognition, behavior and motivation. Moreover, the indicators consisting of seven aspects to measure, that is to say: 1) Rehearsal Strategy, 2) elaboration Strategy, 3) Self-Testing, 4) Assignment Prepare Organization, 5) Time Management, 6) Schedule Planning, 7) Learning atmosphere. The research was conducted at SMKIT DARUL FIKRI North Bengkulu. The researcher found that the results of this study showed a statistically significant effect of the Flipped Classroom Model on self-regulation learning. The increase in student self-regulation was seen in the post-test average score of the experimental class of 95.03, higher than the post-test average value of the control class of 75.68. This found proof that the flipped classroom model had a significant effect on students' self-regulation learning.